Formal Modeling of Cyber-Physical System for Conveyor Sorter - A. Kamarudzaman, N.; Alwi, Saifulza; A. Kasdirin, H. (International Journal of Engineering and Technology, 2018)
Conveyor is usually used in materials handling in manufacturing. Conveyor able to transfer the product from one to another place. In order to use concept of Cyber Physical System (CPS), conveyor have to represent itself to user in cyber and physical. CPS is a communication between cyber and physical of product in real-time system which is user can control the conveyor by using cyber or manually. In this paper, we focused on three goals which are to design CPS model for manufacturing application, modelling the system by using concept Object-Oriented (OO) in any OO software and verification on model using model-checking method. This paper proposes conveyor system as the model for manufacturing. We represent the model as cyber conveyor according to physical conveyor and proposed the methodology how they communicate each other in real time.Â Â  Â
Keywords: cyber-physical system; formal method; industrial automation system; model checking; programmable logic controller.